2006
DOI: 10.1111/j.1365-2133.2006.07415.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy in black people

Abstract: Darker pigmentation of the skin does not impede the identification of single dermoscopic features. As in lighter-skinned populations, dermoscopy in black people can also lead to early and accurate diagnosis of melanoma, thereby significantly reducing the number of unnecessary excisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 11 publications
4
25
0
Order By: Relevance
“…Nevi of skin types II and III are prone to be light to dark brown with multifocal pigmentation ( Figure 5). 44,45 …”
Section: Skin Type-related Nevus Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevi of skin types II and III are prone to be light to dark brown with multifocal pigmentation ( Figure 5). 44,45 …”
Section: Skin Type-related Nevus Patternmentioning
confidence: 99%
“…44,45 Scope et al 38 found a significantly higher frequency of small reticular nevi on children aged 10 to 11 years with dark skin than on those of the same age with fair skin. 38 Our group observed significant skin type-related differences in color and pigment distribution in an adult study population (mean age, 34 years).…”
Section: Commentmentioning
confidence: 99%
“…Giorgi et al 10 Zalaudek et al 11 demonstrated, in a multicenter study, that individuals with different skin types are prone to different nevus types in terms of pigment distribution, color, and, to a certain extent, the global dermoscopic pattern. However, the study was conducted in white people, with skin types I to IV.…”
mentioning
confidence: 98%
“…Particularly, in a recent work De Giorgi et al demonstrated that the same dermoscopic criteria commonly used for white populations could be applied for the analysis of skin lesions in black people with a high rate of reproducibility [146].…”
Section: Dermoscopy On Black Skinmentioning
confidence: 99%
“…Of course, black patients are at lower risk than white individuals of developing melanoma lesions but the diagnosis is often delayed with a poorer prognosis [146].…”
Section: Dermoscopy On Black Skinmentioning
confidence: 99%